The Influence of Socio-Cultural Changes to the Form of Randai Kuantan Art in Kuantan Singingi Riau - Sari, Desti Kumala; Wadiyo, Wadiyo (Catharsis, 2018)
Randai Kuantan is a performing art consisting of art elements, such as, theater, dance, and music from social phenomenon and combination of traditional art of Kuantan Singingi society. Art is a cultural expression of a society that has various functions in accordance with the interests and the condition of the societies. The purpose of this research is to analyze the influence of social change on the form of performance in Randai Kuantan. The science used is Sociology for explaining the factors which influence social change in a society. The method used was interpretative qualitative, and data collection technique was by observation, interview, and document study with primary and secondary data sources. Technique of data validity was by sources triangulation, and the technique of data analysis was by data reduction, presentation, and verification data. The resarch was located in Kuantan Singingi Riau. The social changes are influenced by 2 (two) factors, outside and inside factors and then relates to the role of education, religion, economy, tribes, and social environment of Kuantan Singingi societies. Those factors change the form of Randai Kuantan art including time of performance, members, the location of performance, make up, and costumes. The application of traditional art media are attempts being made to foster awareness of the values and norms that exist in society. In the process of application aspects of the values found in the art of Randai Kuantan is expected to be established and raises awareness for consumer demand. As for the arts as a form of cultural expression community have diverse functions fit the interests and circumstances of society. But basically there are also elements which govern the system of values which formed the society rules, norms, conventions that act as guidelines to achieve the goal. So the arts directly has affected the values and norms that are structurally brings social change on the form of artistry Randai Kuantan. Based on the existing social values were associated in an attempt the formation of individual character in a social environment.